2009
DOI: 10.1007/s00419-009-0387-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical competence of bone-implant systems can accurately be determined by image-based micro-finite element analyses

Abstract: The precise failure mechanisms of bone implants are still incompletely understood. Micro-computed tomography in combination with finite element analysis appears to be a potent methodology to determine the mechanical stability of bone-implant constructs. To assess this microstructural finite element (µFE) analysis approach, pull-out tests were designed and conducted on ten sheep vertebral bodies into which orthopedic screws were inserted. µFE models of the same bone-implant constructs were then built and solved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…In the cadaver study we found a good linear correlation between predicted and measured force at yield (R 2 ¼ 0.75, p¼0.003) and a weaker correlation for the force at pullout (R 2 ¼0.65, p¼0.009) within a VOI of 3 mm diameter, with an octahedral shear strain level of 0.5% and a highly strained bone volume fraction of 30%. A significant but weaker linear correlation was also found for (Wirth et al, 2010;Stadelmann et al, 2013). One possible explanation for this difference is probably due to our osteoporotic model with a load transfer from the comparatively small screws mainly into the cortices.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In the cadaver study we found a good linear correlation between predicted and measured force at yield (R 2 ¼ 0.75, p¼0.003) and a weaker correlation for the force at pullout (R 2 ¼0.65, p¼0.009) within a VOI of 3 mm diameter, with an octahedral shear strain level of 0.5% and a highly strained bone volume fraction of 30%. A significant but weaker linear correlation was also found for (Wirth et al, 2010;Stadelmann et al, 2013). One possible explanation for this difference is probably due to our osteoporotic model with a load transfer from the comparatively small screws mainly into the cortices.…”
Section: Discussionmentioning
confidence: 72%
“…This way we eliminated one of the limitations of other microFE studies, which were based on in vivo microCT scans presenting metal artifact biased peri-implant bone structure (Wirth et al, 2010;Stadelmann et al, 2013). At the same time, the comparatively soft polymer screws did not allow us performing pullout tests for a validation of the model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations